2018
DOI: 10.17507/tpls.0802.02
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Cultural Aspects in the University English Textbook, Well Read 1

Abstract: Abstract-This descriptive study, first, seeks to identify the extent to which the different cultures (source culture, target culture, and international target culture) are represented in the textbook, Well Read 1. This textbook is written by Laurie Blass, Mindy Pasternak, and Elisaveta Wrangell and published by Oxford University Press (2007). Second, it aims to recognize the way these cultural aspects are presented. Third, it ascertains the most dominant and portrayed culture(s) in the prescribed textbook. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The results of this study showed that New Language Leader Pre-intermediate was satisfactory in terms of inclusion of a variety of cultures, which was similar to the findings of the previous research on internationally published textbooks (Alsofi, 2018;Böcü & Razı, 2016;Kayapınar, 2009;Taş, 2010). Since English is taught in many contexts as an international language, the place of culture in the textbooks was questioned by many scholars earlier (Alptekin, 2002;Baker, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The results of this study showed that New Language Leader Pre-intermediate was satisfactory in terms of inclusion of a variety of cultures, which was similar to the findings of the previous research on internationally published textbooks (Alsofi, 2018;Böcü & Razı, 2016;Kayapınar, 2009;Taş, 2010). Since English is taught in many contexts as an international language, the place of culture in the textbooks was questioned by many scholars earlier (Alptekin, 2002;Baker, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…A lack of insight into students' own culture was also detected in the earlier studies (Alsaif, 2016;Alsofi, 2018;Amarian & Tajabadi, 2020;Böcü & Razı, 2016;Çetin Köroğlu, 2016;Dimici et al, 2018;Taş, 2010) that investigated internationally published textbooks. This finding implies that the textbook under investigation and other similar internationally published textbooks could be revised based on the cultural context of the language teaching environment.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations